2014
DOI: 10.1103/physrevb.89.235308
|View full text |Cite
|
Sign up to set email alerts
|

Infrared electrodynamics and ferromagnetism in the topological semiconductorsBi2Te3and Mn-dopedBi2

Abstract: We report on infrared (IR) optical experiments on Bi2Te3 and Mn-doped Bi2Te3 epitaxial thin films. In the latter film, dilute Mn doping (4.5%) of the topologically nontrivial semiconductor host results in time-reversal-symmetry-breaking ferromagnetic order below TC =15 K. Our spectroscopic study shows both materials share the Bi2Te3 crystal structure, as well as classification as bulk degenerate semiconductors. Hence the Fermi energy is located in the Bi2Te3 conduction band in both materials, and furthermore, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 68 publications
3
26
0
Order By: Relevance
“…The frequencies of the α and β phonons (see Tab. I) compare well with reported values 11,15,19 . Between about 0.1-0.8 eV (see Fig.…”
Section: B the Optical Spectroscopy And Analysis Of Optical Datasupporting
confidence: 80%
See 3 more Smart Citations
“…The frequencies of the α and β phonons (see Tab. I) compare well with reported values 11,15,19 . Between about 0.1-0.8 eV (see Fig.…”
Section: B the Optical Spectroscopy And Analysis Of Optical Datasupporting
confidence: 80%
“…The energy of this onset is the same as found in an earlier report of Sehr and Testardi 48 . Chapler et al 15 reported the onset of interband absorption in Bi 2 Te 3 thin films between 140-150 meV at 300 K not too different from our value of 157 meV. Their onset value did not exhibit a significant blue shift with cooling to 10 K. A direct gap was observed in Ref.…”
Section: B the Absorption Edge In Bi2se3supporting
confidence: 48%
See 2 more Smart Citations
“…An insight into the band structure of the surface states of 3D TIs, especially proof for the single Dirac cone, is obtained by varios modifications of the angle resolved photoemission spectroscopy (ARPES) [26][27][28][29][30][31][32] , including spin-resolved and time-resolved ARPES, as well as by time-resolved two-photon photoelectron (2PPE) spectroscopy [33][34][35] , with which an enlightening pictures of fast dynamics in carrier relaxation can be obtained. Further methods, providing important information concerning different growth parameters, nucleation of trigonal islands, and domain alignment of the TI film with respect to the substrate, include scanning (STEM) and high angle annular dark field (HAADF) transmission electron microscopy [36][37][38][39] ; scanning electron microscope (SEM) 40 ; atomic force microscopy (AFM) 41 ; X-ray diffraction (XRD) 42 ; and second harmonic generation 43 as well as infrared or optical spectroscopy 44,45 . However, both spectroscopy and transport investigations do not allow one to analyze the local conductivity in particular at room temperature and materials homogeneity on a large scale.…”
mentioning
confidence: 99%